Buzzing Guardians Buzzing Guardians: Protecting Pollinators in Agricultural Landscapes - Hunasikote Shamappa Venu; Amala Udayakumar; A.N. Shylesha; Timalapur M. Shivalingaswamy (Sociobiology)
In agriculture crop ecosystem, pollination is the foremost fundamental activity performed by fascinating creatures like bees, butterflies, hoverflies, birds and bats that ensures reproductive success in angiosperms. Currently, most of the pollinators are appearing in red data book as their population and abundance depleting in the ecosystem. Their extinction was driven by threats like habitat loss, climate change, urbanization, use of chemical pesticides, pest and diseases. Decline in pollinator population may pose a considerable decrease in global food production and productivity. Effective and efficient conservation strategies are the key elements to mitigate the threats faced by pollinators in the promotion of pollinator resilience. Here we explored a wide range of conservation strategies, which restores the pollinator habitat by following the sustainable agricultural practices, and some policy interventions. Public awareness and collaborative efforts among governments, NGOs, and the private sector are crucial for the successful implementation and adaptation of these conservation strategies. By acclimatizing an integrated, collaborative and convincing approach for pollinator conservation, we can assure and predict the sustainability and productivity of ecosystem, that eventually supports biodiversity and food security.